2013
DOI: 10.1093/jxb/ert041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs associated with seedling root traits and their correlation with plant height in wheat

Abstract: Genetic relationships between plant height and root morphology were investigated in a diverse set of wheat germplasm [199 double-haploid progeny derived from a cross between Avalon and Cadenza (Triticum aestivum L.), Rht near-isogenic lines (NILs), and accessions from the Watkins Collection] to investigate whether Rht genes controlling shoot height also control seedling root growth. A germination paper screen was developed to measure seedling root length (distinguishing seminal axes from seminal lateral roots)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
183
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(204 citation statements)
references
References 28 publications
18
183
2
1
Order By: Relevance
“…Identification of such types of coincident QTLs has been reported in several other studies (Babu et al, 2003;Lanceras et al, 2004;Quarrie et al, 2006;Pushpendra et al, 2007;Bai et al, 2013), which could be due to (i) tight linkages between genes or QTLs that regulate the expression of separate traits or (ii) pleiotropic effect-the same gene or QTL may have an effect on two or more traits simultaneously (Tuberosa et al, 2002). Identification of such types of coincident QTLs has been reported in several other studies (Babu et al, 2003;Lanceras et al, 2004;Quarrie et al, 2006;Pushpendra et al, 2007;Bai et al, 2013), which could be due to (i) tight linkages between genes or QTLs that regulate the expression of separate traits or (ii) pleiotropic effect-the same gene or QTL may have an effect on two or more traits simultaneously (Tuberosa et al, 2002).…”
Section: Discussionsupporting
confidence: 52%
“…Identification of such types of coincident QTLs has been reported in several other studies (Babu et al, 2003;Lanceras et al, 2004;Quarrie et al, 2006;Pushpendra et al, 2007;Bai et al, 2013), which could be due to (i) tight linkages between genes or QTLs that regulate the expression of separate traits or (ii) pleiotropic effect-the same gene or QTL may have an effect on two or more traits simultaneously (Tuberosa et al, 2002). Identification of such types of coincident QTLs has been reported in several other studies (Babu et al, 2003;Lanceras et al, 2004;Quarrie et al, 2006;Pushpendra et al, 2007;Bai et al, 2013), which could be due to (i) tight linkages between genes or QTLs that regulate the expression of separate traits or (ii) pleiotropic effect-the same gene or QTL may have an effect on two or more traits simultaneously (Tuberosa et al, 2002).…”
Section: Discussionsupporting
confidence: 52%
“…QKh-2D.1 and QTw-2D might have been identified due to the presence of other linked genes. The Rht-B1 gene is associated with physiological processes that affect not only plant height but also yield, grain quality, seedling vigor and adaptability to adverse environments (Fischer and Stockman 1986;Gooding et al 1999Gooding et al , 2012McCartney et al 2006;Zheng et al 2010;Bai et al 2013;Zhang et al 2013;Asif et al 2015). This study indicated that Rht-B1b had negative effects on TKW, KW, KDR, TW, DT, and ZEL.…”
Section: Novel Stable Qtls and Qtl Co-segregation With Known Genesmentioning
confidence: 80%
“…QTL for root traits have been mapped in rice (Oryzasativa L.) (Champoux et al 1995;Zheng et al 2000;Courtois et al 2013;Sandhu et al 2013;Liang et al 2013;Dang et al 2014), maize (Zea mays L.) (Lebreton et al 1995;Rahman et al 2011;Osman et al 2013), sorghum (Mace et al 2012), soybean (Zhang et al 2014), Brassica napus , common bean (Phaseolus vulgaris L.) (Ochoa et al 2006;López-Marín et al 2009), Arabidopsis (Fitz Gerald et al 2006), and bread wheat (Spielmeyer et al 2007;Maccaferri et al 2008;Zhang et al 2008;Li et al 2010;Sharma et al 2011;Guo et al 2012;Hamada et al 2012;Ibrahim et al 2012;Ren et al 2012;Bai et al 2013;Christopher et al 2013;Liu et al 2013;Yu and Chen 2013;Zhang et al 2013). In some cases, these studies have suggested possible roles for these QTL in determining plant yield, due to the overlap of QTL for root features with those for traits related to productivity (Johnson et al 2000;Tuberosa et al 2002a, b;Steele et al 2007).…”
Section: Introductionmentioning
confidence: 99%